2023
DOI: 10.2478/pcssr-2023-0012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Teaching Digital Competence and Professional Competencies on the Professional Performance of the Soccer Coach

Abstract: The main objective of this article is to design a structural equation model to evaluate the predictor variables of professional performance in soccer coaches (PPSC), digital teaching competence (DTC) and professional competences of soccer coaches (PCSC). A sample of 612 coaches was taken from the different training levels of the Valencian Community (FFCV) in Spain, managed by UEFA.. The results of the causal relationship model showed a good overall fit of the model. A statistically significant positive relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…It means that digital literacy is a reasonable proclivity for teachers to have to improve their professional performance. These findings are consistent with and confirm the results of previous studies, which suggest that digital literacy has a significant relationship with teachers' professional performance [4,5,[42][43][44][45][46]. Consequently, teachers need to increase their digital literacy to have greater opportunities to improve their professional performance.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It means that digital literacy is a reasonable proclivity for teachers to have to improve their professional performance. These findings are consistent with and confirm the results of previous studies, which suggest that digital literacy has a significant relationship with teachers' professional performance [4,5,[42][43][44][45][46]. Consequently, teachers need to increase their digital literacy to have greater opportunities to improve their professional performance.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, when teachers have an adequate (high) level of digital literacy, including digital competence, usage, and transformation, it can drive their professional performance. Several prior studies also indicated that digital literacy is related to teachers' professional performance [4,5,[42][43][44][45][46]. Therefore, we can propose the first hypothesis (H): H1: Digital literacy directly relates to teachers' professional performance.…”
Section: Digital Literacy and Professional Performancementioning
confidence: 89%
See 1 more Smart Citation
“…In the sport of badminton itself, Indonesia has many coaches who have careers abroad as professional coaches. Professionalism is a process of increasing the qualifications or abilities of members of a profession to achieve the ideal standard criteria of their profession, especially as coaches in sports achievements [14,15,16] . Achieving a professional attitude is certainly not easy, that professionalism requires skills and knowledge in decision making.…”
Section: Introductionmentioning
confidence: 99%